Healthy Status in the Gymnastic Community in West Bandulan, Sukun, Malang - Ratih Paramita Suprapto; Nia Kurnianingsih; Ardani Galih Prakosa; Heri Kristianto; Novita Titis Harbiyanti; Agwin Fahmi Fahanani (Journal of Community Engagement in Health, 2024)
Obesity is a risk factor for various degenerative diseases such as diabetes mellitus and coronary heart disease. Obesity and all degenerative diseases could be prevented by implementing a healthy lifestyle, early detection of risk factors for degenerative diseases, and increasing knowledge about degenerative diseases. Therefore, this service activity aimed to form a healthy community with a program for three consecutive months. Activities included healthy exercise once a week, degenerative disease risk factors screening, and health education. Activities were carried out every Sunday morning for three months located in Bandulan Barat, Sukun District, Malang City. This activity was attended by 40 non-menopausal women. Health screening included waist circumference, random blood glucose, uric acid, cholesterol, and blood pressure. Of the 40 women examined, 39 suffered from central obesity, 6 suffered from hypertension, 4 suspected diabetes mellitus, 5 suffered from hyperlipidemia, and 4 of them suffered from hyperuricemia. As an intervention, participants received education about healthy lifestyles and degenerative diseases, the treatment of hypertension, hyperlipidemia, hyperuricemia, and diabetes mellitus. From healthy screening, central obesity was the most prevalent in this women's community. Healthy exercise community activities with health screening, and health education could be effective strategies for promotive and preventive activities to prevent degenerative obesity.